Distribusi Dan Konsumsi Pendapatan Dalam Hukum Ekonomi Islam - Azra Aurellia; Zihan Putri; Tri Fadhilah (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
The purpose of this article is to examine the distribution of wealth and income in Islamic economic theology. Distribution of wealth in Islam is the transfer of private or public resources to those who are legally entitled to increase the welfare of society in accordance with Islamic law. The process of redistribution of wealth is at the heart of Islam. The obligation to clean up after an affluent party is often seen as compensation for the party's wealth, while the obligation to clean up after a party with a need is seen as an incentive for the party's wealth. This study uses a qualitative approach. Islamic economics proposes a distribution system that does not give preference to any one economic institution and is supported by a set of principles which make it clear that economic stability must be protected at all costs. However, creating economic stability will be difficult if existing institutions such as government and society are not involved. Therefore, the two instruments mentioned above have a very important role, because the distribution policy will be more effective if the two existing institutions work together.